2014
DOI: 10.1002/anie.201410321
|View full text |Cite
|
Sign up to set email alerts
|

From Anilines to Isatins: Oxidative Palladium‐Catalyzed Double Carbonylation of CH Bonds

Abstract: A novel palladium-catalyzed C-H double carbonylation introduces two adjacent carbonyl groups for the synthesis of isatins from readily available anilines. The reaction proceeds under atmospheric pressure of CO with high regioselectivity and without any additives. Density functional theory investigations indicate that the palladium-catalyzed double carbonylation catalytic cycle is plausible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(32 citation statements)
references
References 61 publications
1
30
0
1
Order By: Relevance
“…Recently, Li and co‐workers developed an interesting copper‐catalyzed intramolecular C–H oxidation/acylation of formyl‐ N ‐arylformamides to afford the corresponding indoline‐2,3‐diones 8. Subsequently, a series of methods for transition‐metal‐catalyzed C–H oxidation were documented,9 including the copper‐catalyzed intramolecular oxidative C(sp 3 )–H amidation of 2‐aminoacetophenones,9a the copper‐mediated C–H oxidation and C–N cross‐coupling of 2′‐aminoacetophenones,9b as well as oxidative palladium‐catalyzed CH/NH double carbonylation 9c. Furthermore, several other protocols have been established, including ylide‐mediated carbonyl homologations,10 selenium‐mediated oxidations,11 modified Sandmeyer reactions,12 I 2 ‐catalyzed synthesis of isatins from 2′‐aminoacetophenones,13a and I 2 ‐mediated oxidative amidation of sp, sp 2 , and sp 3 C–H bonds 13b…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Li and co‐workers developed an interesting copper‐catalyzed intramolecular C–H oxidation/acylation of formyl‐ N ‐arylformamides to afford the corresponding indoline‐2,3‐diones 8. Subsequently, a series of methods for transition‐metal‐catalyzed C–H oxidation were documented,9 including the copper‐catalyzed intramolecular oxidative C(sp 3 )–H amidation of 2‐aminoacetophenones,9a the copper‐mediated C–H oxidation and C–N cross‐coupling of 2′‐aminoacetophenones,9b as well as oxidative palladium‐catalyzed CH/NH double carbonylation 9c. Furthermore, several other protocols have been established, including ylide‐mediated carbonyl homologations,10 selenium‐mediated oxidations,11 modified Sandmeyer reactions,12 I 2 ‐catalyzed synthesis of isatins from 2′‐aminoacetophenones,13a and I 2 ‐mediated oxidative amidation of sp, sp 2 , and sp 3 C–H bonds 13b…”
Section: Introductionmentioning
confidence: 99%
“…63 The reaction proceeds under atmospheric pressure of CO and has been proposed to involve an N-H activation by the palladium complex, followed by coordination and insertion of CO. The resulting carbamoyl intermediate undergoes another CO insertion which is followed by a C-H activation to give a palladacycle intermediate.…”
Section: (3+1+1) Annulationsmentioning
confidence: 99%
“…In 2015 the Lei research group reported ap alladiumcatalyzed double carbonylation of anilides to form isatins (Scheme 38). [63] Thereaction proceeds under an atmospheric Scheme 37. Pd-catalyzeda nnulation between ap henylindole and an alkyne.…”
Section: (3+ +1+ +1) Annulationsmentioning
confidence: 99%
“…Lei et al. beschrieben 2015 eine palladiumkatalysierte doppelte Carbonylierung von Aniliden zur Synthese von Isatinen (Schema ) . Die Reaktion wird unter Atmosphärendruck von CO durchgeführt und verläuft vermutlich über eine N‐H‐Aktivierung durch den Palladiumkomplex und anschließende Koordination und Insertion von CO. Das entstehende Carbamoylintermediat geht eine weitere CO‐Insertion ein, der eine C‐H‐Aktivierung zum palladacyclischen Intermediat folgt.…”
Section: Anellierungen Mit Migratorischer Insertion Vor Der C‐h‐aktiunclassified